Experiential Marketing, E-Trust, and E-Loyalty: The Mediating Role of E-Satisfaction among Gen Z Stockbit Users - Bilkis Rafsanjani; Widhy Tri Astuti (SAFE-Network, 2026)
This study examines the determinants of e-loyalty among Generation Z users of the Stockbit digital investment application by analysing the roles of experiential marketing, e-trust, and e-satisfaction. Using a quantitative explanatory design, data were collected from 123 Gen Z respondents residing in Jakarta through an online survey and analysed using PLS-SEM. The results show that experiential marketing and e-trust significantly influence e-satisfaction, confirming that engaging platform experiences and baseline security expectations shape positive user evaluations. Furthermore, experiential marketing and e-satisfaction both have significant effects on e-loyalty, indicating that Gen Z users develop loyalty primarily through meaningful interactions and emotional engagement with the platform. In contrast, e-trust does not significantly affect e-loyalty, either directly or indirectly, suggesting that trust functions only as a hygiene factor—necessary but insufficient to build sustained commitment. E-satisfaction is found to mediate the relationship between experiential marketing and e-loyalty, but not between e-trust and e-loyalty. These findings highlight that experience-driven satisfaction plays a more critical role in retaining digital investment users than perceived security alone. The study provides theoretical insights into loyalty formation in fintech contexts and offers practical recommendations for enhancing user experience to strengthen long-term loyalty.